Ocultação do sujeito passivo na importação mediante interposição fraudulenta de terceiro - Navarro, Carlos Eduardo de Arruda (2016)
The import of goods from foreign countries is an important activity from the Brazilian government, for both tax and regulatory perspectives. Within the regulatory aspect, there are several different authorities performing different jobs, including the customs authorities which are part of the Brazilian Revenue Services. One of the customs authorities’ regulartory interests is the customs control, which means the analysis of the information provided by the importer, such as the actual importer. In order to avoid / punish who is hiding from its condition as an importer, the Brazilian Law has defined, as a customs infraction, the use of a conduit person to hide the actual taxpayer, seller, buyer ou responsible for the import. In this context, this thesis aim to seek two goals: the first one is to present the main characteristics of the analyzed customs infraction, and the second one is to present suggestions and ideas to help Brazilian companies, individuals, and authorities to solve some common problems and doubts on the application of the Law.